Spatial and temporal variations of methane flux measured by autochambers in a temperate ombrotrophic peatland. Issue 5 (23rd May 2014) - Lai, Derrick Y. F.; Moore, Tim R.; Roulet, Nigel T.
Abstract We measured CH4 flux at high temporal resolution with triplicate autochambers from three different plant communities at the ombrotrophic Mer Bleue bog in Canada to investigate the spatial and temporal variations, and factors that related to the CH4 flux. Our results show that seasonal mean CH4 fluxes from the Eriophorum‐dominated community were 1.4–2.2 and 3.7–5.5 times higher than those from Maianthemum/Ledum and Chamaedaphne communities, respectively. Significant interannual variations in CH4 flux were observed in Maianthemum/Ledum and Chamaedaphne communities, attributable to a 55–60% reduction of mean summer (July–September) CH4 flux in 2010 as a consequence of a 5.5–9.0 cm lower mean summer water table compared to 2009. The Eriophorum community showed a much larger rate of increase in CH4 flux with peat temperature in the early growing season than in midsummer, which might be caused by a concomitant increase in root exudation of labile carbon for methanogenesis. Temporal variability of log‐transformed CH4 flux was correlated (r ≥ 0.4) with peat temperature only when water table was less than 20, 30, and 40 cm below the peat surface for Maianthemum/Ledum, Chamaedaphne, and Eriophorum communities, respectively. This difference in water table threshold among communities might partly be related to differences in rooting depth and hence the ability of plants to sustain CH4 flux in dry conditions. These results suggest that modeling of CH4 flux from ombrotrophic peatlands over time should take into account the role of different vegetation types, since the relationships between CH4 emissions and environmental factors vary among vascular plant communities.